Zmodyfikowany indeks rozumienia i stosowania marketingu jako instrument oceny aktywności marketingowej aptek ogólnodostępnych w Polsce - Żak, Konrad (Wydawnictwo Uniwersytetu Wrocławskiego, 2022)
Marketing activity is essential to the operational activities of entities providing pharmaceutical services. However, it raises much controversy due to difficulties in understanding and proper application of particular marketing instruments. This situation, in turn, means that the emerging pathologies in providing pharmaceutical services equate with marketing, which, according to some representatives of the pharmaceutical community, serves only to increase sales for profi t. Sucha narrowing of the marketing role indicates that it is not properly understood and used in pharmacy practice. Marketing should be seen as multifaceted because it is a complex category. Hence, it is defined and understood in various ways. This multifaceted and multidimensional approach to marketing affects the operational activities of community pharmacies, which, understood in various ways, are not always applied lege artis. Bearing in mind the emerging limitations in the proper understanding and use of marketing instruments, the concept of comprehension and marketing application index was created, which was extended and modified by the author (to version 2.0) so that it could be used in pharmacy practice. The article aims to present the idea of the modified comprehension and marketing application index, a system of multi-level and multifaceted assessment of understanding and applying marketing in a pharmacy. The essence of this index isa multidimensional, weighted assessment of the knowledge about the principles of applying marketingand marketing activity carried out during the conducted operating activity. The modified comprehension and marketing application index allows for the objectification and minimization of limitations affecting the assessment of the marketing activity in pharmacies, which results in the rationalization of the classification of marketing management activities.
Keywords: market activity; community pharmacy; comprehension and marketing application index; management; marketing